2022
DOI: 10.35848/1882-0786/ac6ec5
|View full text |Cite
|
Sign up to set email alerts
|

N-polar GaN p-n junction diodes with low ideality factors

Abstract: High-quality N-polar GaN p-n diodes are realized on single-crystal N-polar GaN bulk substrate by plasma-assisted molecular beam epitaxy. The room-temperature current-voltage characteristics reveal a high on/off current ratio of > 1011 at ±4 V and an ideality factor of 1.6. As the temperature increases to 200 °C, the apparent ideality factor gradually approaches 2. At such high temperatures, Shockley-Read-Hall recombination times of 0.32-0.46 ns are estimated. The measured electroluminescence spectrum is dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…For the N-polar Schottky diode, the reverse leakage current is 5.1 × 10 −6 A/cm 2 , and the R on is 314 mΩ•cm 2 . Note that the on-state resistances of our samples are higher than those reported in other works in the literature [14,33,34], possibly originating from the absence of a thermal annealing process for the ohmic contacts. Nevertheless, the purpose of this work is to provide a comparative study on the electrical behaviors between Ga-and N-polar Schottky contacts.…”
Section: Resultscontrasting
confidence: 62%
“…For the N-polar Schottky diode, the reverse leakage current is 5.1 × 10 −6 A/cm 2 , and the R on is 314 mΩ•cm 2 . Note that the on-state resistances of our samples are higher than those reported in other works in the literature [14,33,34], possibly originating from the absence of a thermal annealing process for the ohmic contacts. Nevertheless, the purpose of this work is to provide a comparative study on the electrical behaviors between Ga-and N-polar Schottky contacts.…”
Section: Resultscontrasting
confidence: 62%
“…ZnO and GaN are also important polar materials finding application in various fields. [44][45][46][47][48] The electrochemical nanostructuring of ZnO is less studied because of its low chemical stability. To fill this gap, a cost-effective approach via anodization of the O-face or the Zn-face was proposed for controlled micro-and nanostructuring of polar ZnO crystals, and their luminescence properties were investigated.…”
Section: Optical and Photonic Properties Of Wide-bandgap Semiconducto...mentioning
confidence: 99%
“…[6][7][8][9][10] In the case of n-type GaN on the Ga-polar GaN surface (0001), it has been observed that the carrier concentration is over 1 × 10 20 cm −3 using n-type dopants such as Si or germanium (Ge). 11) On the contrary, several GaN devices, such as vertical GaN power devices, 5,12,13) and N-polar high-electron-mobility transistors, 14,15) require an ohmic contact on the N-polar surface ( ̅ ) 000 1 . For vertical power devices, it is typically necessary to make contact on the N-polar GaN surface, i.e., the backside of the GaN ( ̅ ) 000 1 , substrate with a carrier concentration of around 1 × 10 18 cm −3 directly.…”
mentioning
confidence: 99%